Identifikasi Molekuler Fitoplasma yang Berasosiasi dengan Tanaman Kaktus Hias Opuntia sp. - Ariny Prasetya; Kikin Hamzah Mutaqin; Meity Suradji Sinaga; Giyanto Giyanto (Jurnal Fitopatologi Indonesia, 2017)
Cactus species (Opuntia sp.) is a popular ornamental succulent plant. Some ornamental cactus species in Indonesia showing proliferation and green mosaic pattern symptoms have been reported to be associated with phytoplasma infection. However, further molecular identification for accurate classification of the causal phytoplasma has not been done.  This study aimed to diagnose phytoplasma associated with Opuntia sp. based on molecular methods involving PCR standard combined with nested-PCR, cloning and DNA sequencing. Standard PCR was carried out using P1/P7 primers followed by nested-PCR using R16F2n/R16R2 or fU5/rU3 primer pairs which amplify the 16S rRNA gene targets of 1.2 kb and 880 bp, respectively. Amplified fragment of nested-PCR using R16F2n/R16R2 primers was chosen to be cloned and sequenced for further identification and classification of phytoplasma.  BLASTn analysis showed that the phytoplasma from Opuntia sp. was closely related to 16SrII group. Phylogenetic analysis and in silico RFLP indicated that phytoplasma strain infecting Opuntia sp. was a member of subgroup 16SrII-C (cactus witches’ broom phytoplasma). This is a newly report of cactus witches’ broom phytoplasma on Opuntia sp. in Indonesia.